Pengaruh Pajak Tangguhan dan Tax To Book Ratio Terhadap Kinerja Keuangan Perusahaan Industri Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI Tahun 2015-2019 - Saprudin Saprudin; Elisabet Kristianti; Glory Koeswardhana (Jurnal Ekonomi, 2021)
This study was conducted to determine the effect of deferred tax on financial performance, the effect of tax to book ratio on financial performance and the effect of deferred tax and tax to book ratio simultaneously on financial performance. The variables studied were deferred tax and tax to book ratio as independent variables and financial performance as the dependent variable. The type of research used is using quantitative methods, statistical testing used is multiple linear regression and technical data analysis using classical assumption test. The data collection technique used is library method and documentation method. Furthermore, the sampling technique used was using purposive sampling technique on food and beverage industry companies listed on the Indonesia Stock Exchange in 2015 – 2019. The sample in this study was 25 with 5 companies reporting annual financial reports in a row. in the form of income statements and cash flow statements. The data in this study used the SPSS Version 20 program. The results showed that partially deferred tax had an effect on financial performance. While the tax to book ratio has a significant effect on financial performance. The results of the study simultaneously show that deferred tax and tax to book ratio have a significant effect on financial performance.